Social-pedagogical adaptation of military trainers, which was referred from the ATO, by social-psychological training - Логвінова, О. Г. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The article considers the issues of socio-pedagogical adaptation of soldiers returning from the ATO zone to the new conditions of existence, by means of socio-psychological training; the essence, purpose, and developed guidelines for social workers on the use of funds of social-psychological training in socio-pedagogical work with soldiers who returned from the zone ATO.